Cooperative communications for sleep monitoring in wireless body area networks. Issue 8 (1st April 2016) - Shimly, S.M.; Movassaghi, S.; Smith, D.B.
Abstract : The performance of cooperative receive diversity is investigated, for the wireless body area network (WBAN) radio channel, compliant with the IEEE 802.15.6 Standard, in the case of monitoring a sleeping person. Extensive WBAN measurements near the 2.4 GHz ISM band were used. Up to 7 dB and 20% improvement for two‐hop communications with the use of relays are empirically demonstrated with respect to outage probability and outage duration, with the 3‐branch cooperative selection combining and the 3‐branch cooperative switch‐and‐examine combining.